Left Main Coronary Artery Atresia in Young Man Examined With 99mTc-Tetrofosmin SPECT: A Rare and Challenging Anomaly. (October 2016) - Rampin, Lucia; Rinuncini, Massimo; Zuin, Marco; Rigatelli, GianLuca; Roncon, Loris; Colletti, Patrick M.; Rubello, Domenico
Abstract : Abstract: A young man underwent 99m Tc-tetrofosmin cardiac SPECT/CT for the evaluation of the 8-month history of exertional dyspnea without chest pain. 99m Tc-tetrofosmin SPECT demonstrated absence of perfusion defects and a mildly decreased uptake in post-stress images, consistent with artifact, in the inferior myocardium. Cardiac catheterization showed a large right and a small left coronary artery opacified retrogradely by right collateral vessels without connections between the left main and the left coronary artery. In patients with anomalous coronary arteries, 99m Tc SPECT can shows absence of perfusion defects, in the presence of a collateral circulation.